Elements of Environmental Management - Werner Antweiler (University of Toronto Press, 2014)
Environmental management is becoming increasingly important for businesses. Firms need to manage their direct and indirect impact on the environment, and they need to develop a corresponding corporate environmental strategy. At a managerial level, the interdisciplinary nature of environmental management poses a major challenge because decision-makers are often trained only in one subject area. Environmental managers need to develop competence in a broad range of subject areas, from law to economics to engineering. This book attempts to bridge the gap across these subject areas by making them accessible to a managerial audience. It provides a birdâ€™s-eye perspective on the â€œtools of the tradeâ€ of an environmental manager and develops an interdisciplinary framework for formulating corporate environmental strategy. Many of the environmental management books currently on the market focus quite narrowly on management systems or quite broadly on incorporating sustainability themes into a business context. My book aims at a different audience